MBRS-10. QUIESCENT SOX9-POSITIVE CELLS BEHIND MYC DRIVEN MEDULLOBLASTOMA RECURRENCE. (4th December 2020) - Bolin, Sara; Savov, Vasil; Borgenvik, Anna; Rosén, Gabriela; Olausson, Karl Holmberg; Zhao, Miao; Garancher, Alexandra; Rahmanto, Aldwin Suryo; Hutter, Sonja; Mainwaring, Oliver; Rusert, Jessica; Sundstrom, Anders; et al.
Abstract: Tumor recurrence is the leading cause of death in medulloblastoma, the most frequent malignant pediatric brain tumor. Recurrence occurs when subpopulations of cancer cells evade standard therapy by acquiring features of immune escape, metastatic spread, and treatment resistance. The transcription factor SOX9 correlated with treatment resistance and dissemination in aggressive Group 3 medulloblastoma. By studying paired primary-recurrent medulloblastoma samples and patient-derived xenograft models, we identified rare SOX9-positive slow-cycling, therapy-resistant tumor cells that accumulate in relapses and in metastases. In an inducible transgenic Group 3 tumor model, doxycycline treatment kills all tumor cells by turning MYC off. However, when MYC expression was redirected to the SOX9 promoter, recurrences from rare, dormant SOX9-positive cells developed with 100% penetrance. Expression profiling revealed that recurrences were more inflammatory, metastatic, and showed elevated MGMT methyltransferase levels which depleted recurrent cells when selectively inhibited. Our model explains how recurrences develop from SOX9-induced quiescence in MYC-driven brain cancer.